Pemahaman Mahasiswa Pria Atas Tindakan-Tindakan Pelecehan Seksual Yang Dianggap Normal di Masyarakat The Perspectives of Male Students on Sexual Harassment Acts That Are Considered Normal in Society - Irawan, Andrie; Wijayanti, Anita; Anisah, Laili Nur; Zhafarina, Adlia Nur (EBBANK, 2024)
Colleges have long been regarded as safe places to cultivate individuals with high knowledge and good morals. However, it is regrettable that these educational institutions are not immune to acts of sexual harassment. The forms of sexual harassment vary, including those that have been considered normal and harmless, such as whistling, blowing kisses, or telling inappropriate jokes. However, these actions still have negative effects on the victims, such as feelings of discomfort, anger, or even resentment that can affect the victims' academic performance. One of the reasons perpetrators commit such seemingly trivial acts of sexual harassment is that they are unaware that these actions constitute sexual harassment and can cause discomfort to the victims. This study was conducted to determine whether students understand that certain actions, which have long been normalized, actually constitute sexual harassment. Considering that perpetrators of sexual harassment have predominantly been male, this study was limited to male respondents. Twenty-seven students from four universities participated in this study, which was distributed via Google Forms. The results show that most students are already aware of the acts of sexual harassment that society has normalized. However, there are still some acts of harassment that students are unaware of. It is hoped that continuous education on gender equality awareness will eventually lead to campuses being free of sexual harassment.